Answer:
Look below for the answers.
Explanation:
What I'm going to do is one of these very carefully and leave the other 2 to you. They follow exactly the same pattern and once you see one of them done, you should be able to do any of them.
Six
Step one
Find the common difference.
Two values on the second line are always together so subtract the higher number one from the lower numbered on.
n = 3 and n = 4 on this question are side by side. That is you have f(4) and f(3)
ALWAYS subrract the lower numbered one from the higher numbered one
d = f(4) - f(3) = 60 - 64 = - 4
Step Two
Find the first term.
The first term is ALWAYS f(1). Always. There is never any kind of exception. f(1) in this case is 72
Step Three
Write the general explicit term
The general formula for the explicit Formula is ALWAYS
tn = first term + (n -1)*d
first term = 72
d = - 4 from above.
Explicit formula = 72 + (n - 1)*(-4) So the fifth term is
Example
t5 = 72 + (5 - 1)*(-4)
t5 = 72 + 4*(-4)
t5 =72 - 16
t5 = 56
Step Four
Write the Recursive formula
It is always in the same formal
tn = t_(n - 1) + (common difference)
tn = t_(n - 1) - 4 in this case
Example
Find t2
t2 = t1 - 4
t2 = 72 - 4
t2 = 68
If you do the other two, you can leave them in my PM and I will mark them.